2009
DOI: 10.1158/0008-5472.can-09-0854
|View full text |Cite
|
Sign up to set email alerts
|

Direct Targeting of the Mucin 1 Oncoprotein Blocks Survival and Tumorigenicity of Human Breast Carcinoma Cells

Abstract: The mucin 1 (MUC1) oncoprotein is aberrantly overexpressed by ∼90% of human breast cancers. However, there are no effective agents that directly inhibit MUC1 and induce death of breast cancer cells. We have synthesized a MUC1 inhibitor (called ) that binds to the MUC1 cytoplasmic domain and blocks the formation of MUC1 oligomers in cells. GO-201, and not an altered version, attenuates targeting of MUC1 to the nucleus of human breast cancer cells, disrupts redox balance, and activates the DNA damage response. G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
221
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(231 citation statements)
references
References 36 publications
(62 reference statements)
8
221
2
Order By: Relevance
“…26,38 Accordingly, we developed agents, such as the cell-penetrating peptide , that target the CQC motif and block MUC1-C homodimerization ( Figure 1C). 29,39 Treatment of RPMI8226 cells with GO-203, but not with the control peptide CP-2 ( Figure 1C), resulted in the downregulation of MUC1-C expression ( Figure 1D). We also found that suppression of MUC1-C is associated with decreases in MYC mRNA and protein ( Figure 1D, left and right).…”
Section: Muc1-c Induces Myc Expression In MM Cellsmentioning
confidence: 99%
“…26,38 Accordingly, we developed agents, such as the cell-penetrating peptide , that target the CQC motif and block MUC1-C homodimerization ( Figure 1C). 29,39 Treatment of RPMI8226 cells with GO-203, but not with the control peptide CP-2 ( Figure 1C), resulted in the downregulation of MUC1-C expression ( Figure 1D). We also found that suppression of MUC1-C is associated with decreases in MYC mRNA and protein ( Figure 1D, left and right).…”
Section: Muc1-c Induces Myc Expression In MM Cellsmentioning
confidence: 99%
“…23,25 Accordingly, cell-penetrating peptides have been developed to target the CQC motif. 26,27 The MUC1-C inhibitory peptides include the MUC1-C CQCRRKN sequence linked to 9 Arg residues for cell transduction, such that binding of the peptide to endogenous MUC1-C blocks its homodimerization. [26][27][28] In particular, MUC1-C inhibitor treatment of MM cells growing in vitro and as tumor xenografts is associated with inhibition of growth and induction of late apoptosis/ necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] In particular, MUC1-C inhibitor treatment of MM cells growing in vitro and as tumor xenografts is associated with inhibition of growth and induction of late apoptosis/ necrosis.…”
mentioning
confidence: 99%
“…These findings indicate that up-regulation of C1GALT1 promotes breast tumor growth through modified glycophenotypes of MUC1-N and MUC1-C signaling pathway. An inhibitory small peptide GO-201 specifically targeting the CQC residues of MUC1-C cytoplasmic domain has been well established to prevent MUC1-C dimerization and activation in breast cancer development [29,41]. Indeed, we found that GO-201 significantly suppressed C1GALT1-mediated cell viability and inhibited MUC1-C translocation into the nucleus in T47D and MCF-7 cells.…”
Section: Discussionmentioning
confidence: 66%